Enhancing undergraduates’ career preparedness: environmental determinants and mediating role of resilience - Ainullutfi Azzman; Teoh Sian Hoon; Leele Susana Jamian; Nurhayani Romeo; Mohammad Hafiz Mohd Yusof; Koo Ah Choo (International Journal of Evaluation and Research in Education (IJERE), 2026)
Current environmental changes, combined with personal challenges, require further study to address the existing knowledge gap in career preparedness. Hence, this study aims to examine determinants of undergraduates’ career preparedness by integrating environmental and psychological factors within an extended theoretical framework. Specifically, this study investigates the effects of resilience as a mediator in the relationship between environmental factors and career preparedness. This study used stratified purposive sampling to capture final-year undergraduates from universities in three main structures, namely research universities, non-research public universities, and private universities. A total of 409 undergraduates participated in this study. A correlational research design was employed for the investigation of the relationships. Structural equation modeling (SEM) was used to test the hypothesized relationships and mediation effects. The results indicated that environmental factors were a robust predictor of resilience (effect size, f2=1.377) and exerted a small but significant direct effect (f2=0.051) on career preparedness. Furthermore, resilience strongly predicted career preparedness (f2=0.450). Overall, the findings show that resilience mediates the relationship between environmental factors and career preparedness. This study contributes to the literature by demonstrating that resilience-based activities, such as career planning and goal-setting sessions, should be focused on undergraduates who are participating in a constructive environment.